Leveraging Monopoly Power by Degrading Interoperability: Theory and Evidence from Computer Markets. - Genakos, Christos; Kühn, Kai‐Uwe; Van Reenen, John (Economica, 2018)
When will a monopolist have incentives to leverage her/his market power in a primary market to foreclose competition in a complementary market by degrading compatibility/interoperability of her/his products with those of her/his rivals? We develop a framework where leveraging extracts more rents from the monopoly market by ‘restoring’ second‐degree price discrimination. In a random coefficient model with complements, we derive a policy test for when incentives to reduce rival quality will hold. Our application is to Microsoft's alleged strategic incentives to leverage market power from personal computer to server operating systems. We estimate a structural random coefficients demand system that allows for complements (personal computers and servers). Our estimates suggest that there were incentives to reduce interoperability that were particularly strong at the turn of the 21st century.